Root Border Cells as a Convenient Single Cell System to Study Plant-Environmental Interactions: A Case Study for Aluminum Tolerance - Feng, Yingming; Chen, Xingyun; Li, Xuewen; Li, Yalin; Nong, Wei; Tang, Jiao; Han, Hongxiang; Shi, Lei; Shabala, Sergey; Yu, Min (Frontiers in Soil Science, 2022)
Root border cells (RBCs) are a group of cells originated from the root cap meristem, which are developed by genetic regulation and play a variety of biological functions. Being composed of a homologous single cell population with high metabolic activity and intact cell walls, RBCs represent a highly useful tool for studying various aspects of plant mineral absorption and utilization, as well as plant-soil-microbiome interactions in the rhizosphere. Research on RBCs also promise to become a hotspot in the context of understanding root adaptive responses to hostile environments. In order to take advantages of RBCs as an ideal single cell system in plant-environmental interactions, we summarized the production and function of RBCs and built-up the methodology for RBCs culturing, purification, and quantity control for plant research. The latter is done by using a case study of application of RBCs to study mechanisms of Al toxicity in plants. This work offers plant scientists a new cognition of adopting RBCs as a convenient single cell system for the multidisciplinary research included (but not limited to) plant physiology, development and genetics, nutrition, and stress and adaptation.